2022
DOI: 10.1590/s1678-9946202264062
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalizations for COVID-19 in a tertiary hospital in Brazil: a parallel with vaccination

Abstract: This study aimed to evaluate the COVID-19 hospitalizations in a tertiary hospital by age group and month, considering the introduction and the advance of the vaccination against the disease. The laboratory-confirmed COVID-19-associated hospitalizations among people aged 20 years or older, that occurred between March 2020 and June 2021, were distributed by month of symptom onset and age group. The proportion of hospitalizations by age group was calculated for the year 2021. The proportions were compared using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…In line with this finding of the present study, the results of the studies A. Christie et al (2021) [19], M. L. Salomão et al (2022) [20] as well as Emre Özgen et al (2023) [21] showed that general vaccination of COVID-19 was associated with a change in the age range of patients hospitalized in corona wards. So that after the start of general vaccination of COVID-19, most of the patients hospitalized in corona wards were in the age group of less than 50 years.…”
Section: Discussionsupporting
confidence: 91%
“…In line with this finding of the present study, the results of the studies A. Christie et al (2021) [19], M. L. Salomão et al (2022) [20] as well as Emre Özgen et al (2023) [21] showed that general vaccination of COVID-19 was associated with a change in the age range of patients hospitalized in corona wards. So that after the start of general vaccination of COVID-19, most of the patients hospitalized in corona wards were in the age group of less than 50 years.…”
Section: Discussionsupporting
confidence: 91%